Penegakan Hukum Pemilu terhadap Praktik Politik Uang di Indonesia - Siti Yuliana Novitasari; Fathorrahman Fathorrahman; Ainun Najib (Hukum Inovatif : Jurnal Ilmu Hukum Sosial dan Humaniora, 2025)
The provisions of the 1945 Constitution Article 1 paragraph (3) "The State of Indonesia is a State of Law". In addition to being a state of law, Indonesia is also a democratic state. In the concept of democracy, the government of a country is a government of the people, by the people, and for the people (principle of democracy). One of the important moments for the state of Indonesia to adopt a democratic system is the implementation of elections. Elections are also a means to encourage accountability and public control over the state, direct elections will make prospective leaders in the election contest do various ways to attract public sympathy to be able to vote for them. Even with methods that violate the constitution are also carried out. As is often the case in society during the election period, namely money politics . Legal regulations related to money politics in Law no. 7 of 2017 concerning elections include several special articles that prohibit the practice of money politics, but legal loopholes in election regulations include unclear definitions and ambiguous exceptions. Law enforcement against the practice of money politics in Indonesia still faces many challenges. This study uses a library study method supported by relevant research. The results of the study show that the root of the problem of the emergence of money politics is the existence of legal loopholes, weak supervision and a proportional election system that opens up opportunities for the development of money politics. The problem of money politics needs to be analyzed to obtain an effective strategy in preventing it. Money politics is not in accordance with the principles of democratic theory which demands freedom and justice. Elections are said to be fair if all people have the same right to choose leaders by not violating the rule of law.